Design and key parameter optimization of an agitated soybean seed metering device with horizontal seed filling - Jia, Honglei; Chen, Yulong; Zhao, Jiale; Guo, Mingzhuo; Huang, Dongyan; Zhuang, Jian (International Journal of Agricultural and Biological Engineering, 2018)
Since the low seed filling speed of mechanical seed metering devices reduces the low qualified rate of seed spacing during high-speed practices, it is significant to design agitated seed metering devices with horizontal seed filling that are suitable for high-speed practices. The combination of horizontal seed filling and agitated seed filling can accelerate the seed filling of mechanical seed metering devices, and improve the qualified rate of seed spacing during high-speed practices. In this study, theoretical analysis, discrete element method-based simulation and indoor bench test verification were conducted to investigate how key parameters of the agitated seed metering device with horizontal seed filling (angles, installation position and number of agitating plates, diameters of convex spoons) would affect the characteristics of soybean seed movement, seed number and seeding performance (qualified index, multiple index, missing seeding index) under different working speeds. Computer-based simulation, test design and regression analysis were combined to analyze the population moving rules and optimize the design parameters of seed metering devices. Based on the test scheme as designed, simulations were conducted on Fluent EDEM, and the optimal angle of the agitating plates was determined by analyzing the population migrating rules. Regression equations were established through the regression of test results, and used to find out the optimal design parameters (diameter of convex spoon, positions and number of agitating plates) of seed metering devices. Then the optimal parameter combination among different working conditions was determined that the angle, position and number of agitating plates were 30°, 24.4 mm, and 13, respectively, and the diameter of convex spoon was 11.0 mm. With the optimal parameter combination and at the seeding speed of 12 km/h, the qualified index, multiple index and missing seeding index were 93.1%, 2.1% and 4.8%, respectively. Under high-speed practices, the new seed metering device was not significantly different from the pneumatic seed metering device, but significantly outperformed the mechanical seed metering device. Keywords: soybean seed metering device, horizontal seed filling, agitated seed filling, high-speed precision seeding, discrete element method DOI: 10.25165/j.ijabe.20181102.3464 Citation: Jia H L, Chen Y L, Zhao J L, Guo M Z, Huang D Y, Zhuang J. Design and key parameter optimization of an agitated soybean seed metering device with horizontal seed filling. Int J Agric & Biol Eng, 2018; 11(2): 76–87.